A mongol kor ismeretlen történetei: The Rise of the Mongols: Five Chinese Sources. Edited and translated, with an introduction, by Christopher P. Atwood (with Lynn Struve). Indianapolis: Hackett Publishing Company, 2021 - Apatóczky, Ákos Bertalan (Távol-keleti Tanulmányok, 2022)
Apatóczky Ákos Bertalan recenziója Christopher P. Atwood (szerk., ford., bev.) The Rise of the Mongols: Five Chinese Sources című munkájáról.